Effects of enzymatic hydrolysate of locust bean gum on digestibility, intestinal morphology and microflora of broilers. Issue 1 (24th November 2019) - Xie, Jingjing; Wang, Zhongcheng; Cui, Hu; Nie, Hao; Zhang, Tietao; Gao, Xiuhua; Qiao, Yu
Abstract: To investigate the effects of different levels of enzymatic hydrolysate of dietary locust bean gum on nutrient digestibility, intestinal morphology and microflora of broilers, a total of 768 one‐day‐old Arbor Acres (AA) broiler chicks were randomly divided into 6 treatments with 8 replicates per treatment and 16 birds per replicate. The treatments were as follows: (1) CON, basal diet; (2) ANT, basal diet +62.5 mg/kg flavomycin; (3) LBG, basal diet +0.1% locust bean gum; (4) ELBG‐0.1, basal diet +0.1% enzymatic hydrolysate of LBG; (5) ELBG‐0.2, basal diet +0.2% enzymatic hydrolysate of LBG; and (6) ELBG‐0.3, basal diet +0.3% enzymatic hydrolysate of LBG. The digestibilities of ether extract, crude protein and dry matter were increased ( p < .01) in broilers fed the ELBG‐0.3 diet compared with the CON and LBG diets on day 21. Duodenal villus height and the ratio of the villus height to crypt depth were greater ( p < .01) in broilers fed the ELBG‐0.3 diet than the CON, ANT and LBG diets. Jejunum villus height was higher ( p < .05) in broilers fed the ELBG‐0.2 and ELBG‐0.3 diets than the CON diet. The number of caecal Escherichia coli was reduced ( p = .01) in broilers fed the ELBG‐0.2 and ELBG‐0.3 diets compared with the CON diet. The number of caecal Lactobacilli was greater ( p < .05) in broilers fed the ELBG‐0.3 diet than the CON and ANT diets. In summary, the addition of 0.3% locust bean enzymatic hydrolysate can increase the surface area of intestinal villi and the number of beneficial bacteria, inhibit the proliferation of harmful bacteria, maintain the balance of intestinal microflora and improve the digestibility of nutrients.